ANALISIS DETERMINAN KETIMPANGAN PENDAPATAN DI PULAU SUMATERA - Shofi Yuni Fitri; Mike Triani (Universitas Negeri Padang, 2025)
This study aims to analyze the determinants of income inequality in Sumatra Island. The variables examined consist of GDP per capita, agricultural sector GDP, agricultural employment, school participation rate, open unemployment rate, and female labor force participation across 10 provinces in Sumatra from 2015 to 2022. This research employs panel data analysis, and based on the model selection tests conducted, the Fixed Effect Model (FEM) was identified as the most appropriate model.The results indicate that GDP per capita has a negative and significant effect on income inequality, implying that higher regional income contributes to reducing inequality in Sumatra. Likewise, the school participation rate and female labor force participation show negative and significant effects, suggesting that better access to education and greater involvement of women in the labor market play an essential role in narrowing the income gap.Meanwhile, agricultural employment has a negative but insignificant effect on income inequality, indicating that the agricultural labor sector has not yet contributed meaningfully to reducing inequality. Furthermore, agricultural GDP and the open unemployment rate have positive but insignificant effects, demonstrating that increases in these variables do not have a substantial impact on income distribution. Overall, the findings highlight the importance of economic growth, education, and female workforce participation in addressing income inequality in Sumatra.